In Response to 'Options for the Treatment of Gemcitabine-Resistant Advanced Pancreatic Cancer: Are We There Yet?' - Gounaris, Ioannis; Zaki, Kamarul; Corrie, Pippa (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Addenbrooke’s Hospital. Cambridge, United Kingdom.